Analysis of Primary Stakeholders Participation in Forest Resources Management: The Case of the Krokosua Hills Forest Reserve, Ghana - Adams, Marshall Alhassan (2012)
A thesis Submitted to the Department of Materials Engineering,Kwame Nkrumah University of Science and Technology,in partial fulfillment of the Requirements for the Degree of Master of Science in Environmental Resource Management, 2010